Online-based Physiotherapy UKOM TryOut and Guidance Program in 2023: Program TryOut dan Bimbingan UKOM Fisioterapi Berbasis Online Tahun 2023 - Naufal, Adnan Faris; Arwida, Neriya; Ardiani, Savilla Dara; Puspitaningrum, Dinda Ayudya (Prosiding University Research Colloquium, 2023)
The Online-Based TryOut and Guidance Program for Physiotherapy Competency Examination (UKOM) in 2023 is an initiative aimed at preparing participants for the Physiotherapy UKOM from various physiotherapy institutions across Indonesia. The program was held in August 2023 and involved 145 participants. Through online platforms such as Zoom Meetings, participants were granted access to learning materials, TryOut tests, and direct guidance from experienced physiotherapy instructors. The results of this program included an improved understanding of the material, enhanced examination skills, inter-institutional collaboration, and increased accessibility for participants from across the nation. Consequently, the program has provided significant benefits in preparing participants for the Physiotherapy UKOM, enhancing the quality of human resources in the field of physiotherapy, and opening opportunities for cross-institutional collaboration that could potentially support advancements in this field in Indonesia. Programs like this demonstrate the potential for further development in the context of physiotherapy education and certification in the future.